Performance Analysis of Network Emulator Based on the Use Of Resources in Virtual Laboratory - Yuri Ariyanto; Yan Watequlis Syaifudin; Budi Harijanto (Proceeding of the Electrical Engineering Computer Science and Informatics, 2017)
A network emulator is a software in its environment mimicking the functions and habits of the original network. Problems often encountered in doing research on computer networks is a problem of design and trial scenarios that require software and hardware enough to implement such a network  scenario  similar  to  a  real  scenario.  Using  virtual machine technology is expected to solve the problem. Netkit supports experiments with various network technologies and can support other technologies necessary for certain network experiments. This study uses a network emulator with netkit, where it is freely available and built based on Linux User Mode. Netkit  allows  users  to  experiment  with  complex   computer network scenarios that can be easily implemented using linux. The experimental research is done by making the design first. The design is used to implement the routing process, to connect 4 different network addresses. On the Netkit implementation of the design, it is implemented by creating a virtual routing lab based on   data   from   computer   network   topologies.   The   virtual laboratory implementation of this research routing is based on a network topology scenario. The results of these virtual routing lab experiments, the routing process runs well on the network based on predetermined test scenarios, with the occurrence of connections between different network addresses..In the end the virtual routing lab implementation works well, with performance analysis results from the netkit emulator on the use of computer resources showing Usage CPU usage of 0% and Memory Usage averaging 20942.8k test time for 12 minutes. The results of this trial is very helpful for administrators before the implementation on the real network